Profitability of Technical Currency Speculation. The Case of Yen-Dollar Trading 1976-2007 - Stephan Schulmeister (Austrian Institute of Economic Research (WIFO), 2008)
The paper investigates the profitability of 1,024 moving average and momentum models and their components in the yen-dollar market. It turns out that all models would have been profitable between 1976 and 2007. The models produce more single losses than single profits. At the same time, the size of the single profits is on average much higher than the size of single losses because profitable positions last two to six times longer than unprofitable positions. Hence, the profitability of technical currency trading is exclusively due to the exploitation of persistent exchange rate trends. These results hold also when technical trading is examined over subperiods. The models which perform best over the most recent subperiod are in most cases significantly profitable also ex ante. However, the profitability of technical currency trading based on daily data has declined since the mid 1990s, and it has disappeared since 2000.
Keywords: 330; Exchange rate; Technical trading; Speculation; Währungsspekulation; Yen; US-Dollar; Anlageverhalten; Kapitaleinkommen; Wechselkurs; Volatilität; Schätzung; Welt